Pembuktian Dalam Perkara Permohonan Izin Poligami di Indonesia (Studi Kasus Putusan Nomor 3977/Pdt.G/2019/PA.Dpk) - Abednego Ozora; Reinaldy; Renee Lim; Rizky Karo Karo; Samuel Kaban Solavide (Fakultas Hukum Universitas Islam Indonesia, 2024)
In marriage, rights and obligations arise that bind both parties in the hope of achieving inner peace and creating a happy and prosperous family. Marriage is seen as a noble thing in society's view which is based on a reciprocal bond of love and affection between a man and a woman. However, in marriage, there is a problem that is being discussed to this day, namely the issue of polygamy. Polygamy is the practice of a man having more than one wife simultaneously. In this research, we will discuss the Case Study of Decision Number 3977/Pdt.G/2019/PA.Dpk. This research was conducted to understand how evidence works in Civil Procedure Law, study the legal basis and procedures for polygamy in Indonesia, and analyze the relevance of the evidence submitted to the judge's consideration in the application for a polygamy permit in the decision adopted by the authors. Based on the research, it is concluded that the law of evidence in civil cases is included in the HIR and BW, and plays an important role in the trial process to reveal legal facts. Furthermore, the legal basis for polygamy is regulated in the Marriage Law and Presidential Instruction Number 1 of 1991 concerning the Dissemination of the Compilation of Islamic Law. Through this research, it is also concluded that in this case study,, the Proof of Statement of Capability for Marriage/Polygamy fulfilled the cumulative requirements related to polygamy according to the Law, but the alternative requirements related to the inability of the requested party were not met in the trial. In addition, witness testimony proves that the Petitioner has the ability to guarantee and finance the household needs of his wife and children.